A STUDY PROTOCOL FOR A DOUBLE-ARM RANDOMISED CONTROLLED TRIAL TO EVALUATE THE ANAESTHETIC EFFICACY OF A NOVEL TOPICAL AYURVEDIC EMULGEL DURING NEONATAL VENIPUNCTURE (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Effective pain management in neonates during procedures such as venipuncture is critical to minimise potential adverse neurodevelopmental and psychological consequences. Conventional synthetic topical anaesthetics, while effective, may pose safety concerns in this vulnerable population. This study protocol proposes to evaluate a novel topical ayurvedic emulgel (NTAE) containing Anacyclus pyrethrum (Akarkarabha) and Syzygium aromaticum (Lavanga) as a potentially safer alternative to standard lidocaine–prilocaine cream (LPC) for neonatal venipuncture. Objectives: The primary objective is to evaluate the anaesthetic efficacy of NTAE in reducing pain during venipuncture in neonates. Secondary objectives include comparison with LPC and assessment of the incidence of local adverse effects following topical anaesthetic application. Methods: This will be a single-centre, prospective, randomised-controlled, parallel-group, single-blind clinical trial. A maximum proposed sample size of one hundred neonates will be randomly assigned to either the intervention group receiving NTAE or the control group receiving LPC. The trial will be conducted in two phases based on application duration: Phase I (30-minute application) and Phase II (60-minute application), in accordance with the revised IEC-approved protocol. The study drug will comprise Anacyclus pyrethrum ethanol extract and Syzygium aromaticum oil formulated as an emulgel using standardised procedures. Pain will be assessed using the Neonatal Infant Pain Scale (NIPS) and the Neonatal Facial Coding System (NFCS), along with monitoring of physiological parameters such as heart rate and oxygen saturation. Conclusion: This study protocol aims to generate evidence regarding the feasibility, efficacy, and safety of an ayurvedic topical anaesthetic formulation for neonatal venipuncture and may inform the design of future integrative and multicentric clinical trials in neonatal pain management.